PROTECTIVE ACTIVITY STUDY OF A CANDIDATE VACCINE AGAINST ROTAVIRUS INFECTION BASED ON RECOMBINANT PROTEIN FliCVP6VP8 - I. V. Dukhovlinov; E. G. Bogomolova; E. A. Fedorova; A. S. Simbirtsev (Медицинская иммунология, 2016)
Rotavirus infection is among leading causes of severe diarrhea which often leads to severe dehydration, especially, in children under 5 years old. In Russia, the incidence of rotavirus infection is constantly increased, due to higher rates of actual rotavirus infection cases and improved diagnostics of the disease. Immunity to rotavirus is unstable, thus causing repeated infections intra vitam. Anti-infectious resistance in reconvalescents is explained by induction of specific IgM, IgG, and, notably, IgA antibodies. Due to absence of market drugs with direct action against rotavirus, a rational vaccination is considered the most effective way to control the disease. Currently available vaccines for prevention of rotavirus infection are based on live attenuated rotavirus strains, human and/or animal origin, which replicate in human gut. Their implementation may result into different complications. Meanwhile, usage of vaccines based on recombinant proteins is aimed to avoid risks associated with introduction of a complete virus into humans. In this paper, we studied protective activity of candidate vaccines against rotavirus.In this work we studied protective activity of a candidate vaccine against rotavirus infection based on recombinant FliCVP6VP8 protein which includes VP6 and VP8, as well as components of Salmonella typhimurium flagellin (FliC) as an adjuvant. Different components are joined by flexible bridges. Efficiency of the candidate vaccine was studied in animal model using Balb/c mice. We have shown high level of protection which occurs when the candidate vaccine is administered twice intramuscularly. Complete protection of animals against mouse rotavirus EDC after intramuscular immunization with a candidate vaccine was associated with arising rotavirus-specific IgA and IgG antibodies in serum and intestine of immunized animals. The efficacy of candidate vaccine based on recombinant protein FliCVP6VP8 against rotavirus infection was comparable to that of commercial Rotarix® vaccine (Glaxo Smith Kline), however, with higher safety of the candidate vaccine, due to absence of live virus in its composition. Hence, the results obtained justify further pre-clinical studies of the candidate vaccine based on a recombinant protein.